Using Social Network Analysis to Identify Successful Relationship Patterns Within Sexual Assault Response Teams (SARTs). (June 2019) - Greeson, Megan R.; Watling Neal, Jennifer; Campbell, Rebecca
The current study used social network analysis (SNA) to examine relationships within three effective Sexual Assault Response Teams (SARTs) that coordinate the response of legal, medical, and advocacy organizations to sexual assault. Within each SART, organizations reported on each other member organization valuing their role, serving as a resource to their work, and communication outside of official meetings. Across the SARTs, there was high connectedness and reciprocity and low to moderate dependence on one organization to drive relationships. However, there was dependence on a subgroup of organizations to drive additional communication relationships. Implications for managing relationships in SARTs are discussed.